'Cheaters and Stalkers': Accusations in a classroom. (February 2015) - Niemi, Kreeta; Bateman, Amanda
This article explores accusations as collaboratively accomplished in classroom peer interactions in the absence of a teacher. The analysis shows how the children use local classroom rules and teacher authority as resources and warrants to invoke multi-layered moral orders and identities, and hold one child accountable through accusations about their behavior. The accused children are categorized in a duplicative way with morally degrading descriptions and as out-group members. This article argues that understanding children's accusations requires understanding of how such interactions compose and reflect the school context that is co-produced through the implementation of accountable ways in which to behave.